Complementary Prognostic Value of Pelvic Magnetic Resonance Imaging and Whole-Body Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Pretreatment Assessment of Patients With Cervical Cancer. Issue 8 (October 2015) - Sala, Evis; Micco, Maura; Burger, Irene A.; Yakar, Derya; Kollmeier, Marisa A.; Goldman, Debra A.; Gonen, Mithat; Park, Kay J.; Abu-Rustum, Nadeem R.; Hricak, Hedvig; Vargas, Hebert Alberto
Abstract : Objective: The aim of this study was to evaluate the incremental prognostic value of pelvic magnetic resonance imaging (MRI) and whole-body 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) findings compared with clinical-histopathologic factors in patients with newly diagnosed cervical cancer. Methods: The institutional review board approved this retrospective study of 114 patients (median age, 40.6 years) with International Federation of Gynecology and Obstetrics (FIGO) stage I-IVB cervical cancer who underwent pretreatment MRI and PET/CT. All scans were reviewed for locoregional tumor extent, pelvic or/and para-aortic lymphadenopathy, and distant metastases. Univariate Cox proportional hazard regression was performed to evaluate associations between clinical-histopathologic factors, imaging findings, and progression-free survival (PFS). Multivariate models were built using independent predictors for PFS. Harrell C was used to measure concordance ( C index). Results: Forty patients progressed within a median time of 10.4 months (range, 0.4–40.3 months). At univariate analysis, age, FIGO stage, tumor histology, tumor grade, and all MRI and PET/CT features were significantly associated with PFS ( P < 0.0001 to P = 0.0474). A multivariate model including clinical and imaging parameters (parametrial invasion on MRI and para-aortic lymphadenopathy/distant metastases on PET/CT) had significantly higher concordance for predicting PFS than a model including clinical parameters only ( C index: 0.81 [95% confidence interval, 0.75–0.87] vs 0.68 [95% confidence interval, 0.59–0.78]; P < 0.001). The comparison of C indices for the combined clinical and imaging model approached significance when compared with a FIGO stage model ( C index: 0.81 [95% confidence interval, 0.75–0.87] vs 0.75 [95% confidence interval, 0.69–0.82]; P = 0.058). Conclusions: In patients with newly diagnosed cervical cancer, a prognostic model including combined MRI and PET/CT findings provides information that complements clinical and histopathologic factors.